Microcatheter-Assisted Trabeculotomy Combined With Deep Sclerectomy and Trabeculectomy in Young to Middle-Aged Adults With Advanced Primary Open-Angle Glaucoma: 1-Year Result - Zhang, Hengli; Yan, Xiaowei; Li, Fan; Ma, Lihua; Geng, Yulei; Jiao, Kexin; Tang, Guangxian (Frontiers in Medicine, 2021)
Objective: We aimed to evaluate the safety and clinical efficacy of ab externo microcatheter-assisted trabeculotomy combined with deep sclerectomy and trabeculectomy (MATT-DS-Trab) in the surgical management of advanced primary open-angle glaucoma (POAG). Methods: According to the inclusion criteria, we retrospectively collected and analyzed 37 POAG cases in advanced stage who received MATT-DS-Trab. The intraocular pressure (IOP), best corrected visual acuity (BCVA), use of anti-glaucoma drugs, shape of the filtering bleb, size of the scleral lake, complications, and the surgical success rate were recorded. Results: The mean IOP was 37.50 ± 8.11 mmHg before the operation, while it depleted to 10.08 ± 2.01 and 11.43 ± 2.07 mmHg at 1 week and 12 months after the operation, respectively (both P < 0.001 compared to preoperative IOP). From none to two kinds of anti-glaucoma drugs were used 12 months after surgery on the patients, which were significantly reduced compared with that preoperatively (P < 0.001). An L-type filtering bleb was the main form at all time points after the operation. At 12 months following surgery, an F-type filtering bleb accounted for 5.41% and no E-type filtering bleb was recorded. The length and height of the scleral lake shrunk with time, but there was no statistical significance (P > 0.05). Also, there was no correlation between the size of the scleral pool and the IOP (P > 0.05). At 12 months after the operation, the complete success rates were 94.59, 83.78, and 72.97% according to standards A (≤18 mmHg), B (≤15 mmHg), and C (≤12 mmHg), respectively. Intraoperative complications were mainly anterior chamber hemorrhage, and no complications related to the filtration bleb were observed after the operation. Conclusion: Based on multichannel mechanisms, MATT-DS-Trab is able to effectively reduce IOP in advanced POAG patients, with few serious complications and a high success rate.